A tissue-bioengineering strategy for modeling rare human kidney diseases in vivo - J. O. R. Hernandez (Nature Portfolio, 2021)
The lack of animal models for some human diseases precludes our understanding of disease mechanisms and our ability to test new therapies in vivo. Here the authors present a tissue bioengineering strategy for the study of a rare kidney tumor called angiomyolipoma, in vitro and in vivo, using patient-derived hiPSCs.